Combined Effect of Parthenolide and Various Anti-cancer Drugs or Anticancer Candidate Substances on Malignant Cells in vitro and in vivo - Wyrebska, Anna; Gach, Katarzyna; Janecka, Anna (Mini Reviews in Medicinal Chemistry, 2014)
Despite the enormous advances in the development of new drugs, the efficacy of current antitumor therapies is still quite limited, most likely because of the high degree of cancer heterogeneity and cell signaling complexity. As a single drug does not necessarily eradicate the cancer, the use of drug combinations has been proposed, and numerous studies have already been conducted to examine the efficacy of this strategy. In the last decade, parthenolide, a plantderived sesquiterpene lactone, was extensively studied and its potential to inhibit cancer cell growth in vitro was well documented. More recently, antitumor effects exerted by parthenolide in combination with various drugs routinely used in cancer treatment have been investigated in several laboratories. In this article studies that are underway in an attempt to improve the anticancer efficacy of chemotherapies through combination strategies involving parthenolide are summarized.
Keywords: NF-κB